Nano-bio Interactions - Reichenfelser, R.; Punz, E.; Joubert, I.A.; Geppert, M.; Himly, M. (Open Schools Journal for Open Science, 2020)
Due to theri extremely small size, nanoparticles display a unique set of characteristics, which differ significantly form bigger moieties. These characterstics also shape their interaction with biological entities. Theri large surface-to-volum area, for instance, makes paritcles in the nano- and micro-range very reactive. Clubmoss spores are an example of naturally occuring microparticles.